1975
DOI: 10.1051/rnd:19750232
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Oestrous Cycle in Friesian Heifers With Ici 80,996

Abstract: SUMMARYTwo single intramuscular injections of 500 t t g of ICI 8 0 , 99 6 separated by a period of i days was shown to be an effective method of controlling oestrus and ovulation in cycling heifers. One hundred and seventy one of one hundred and seventy five heifers exhibited oestrus between 4 8 and g6 hours, and no fewer than 159 of these came into heat between 4 8 and 72 hours after the second injection. Changes in plasma concentrations of LH, progesterone and oestradiol-17P around the oestrus following lute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These unpredictable responses mean that either oestrous detection or double insemination of a herd is necessary to achieve normal fertility (Nancarrow and Cox 1976). Following prostaglandin injection the time course of luteolysis is uniform (Cooper and Rowson 1975) indicating that variations in oestrous responses are primarily due to differences in the growth and development of mature Graafian follicles capable of ovulating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These unpredictable responses mean that either oestrous detection or double insemination of a herd is necessary to achieve normal fertility (Nancarrow and Cox 1976). Following prostaglandin injection the time course of luteolysis is uniform (Cooper and Rowson 1975) indicating that variations in oestrous responses are primarily due to differences in the growth and development of mature Graafian follicles capable of ovulating.…”
Section: Introductionmentioning
confidence: 99%
“…1972). However, quantitative data on the rate of follicular growth in the cow is not available and is clearly an essential to understanding the variability in the time of ovulation following surgical (Brock and Rowson 1952) or chemical (Cooper and Rowson 1975) destruction of the corpus luteum. The aim of this study was to quantitatively appraise ovarian follicular growth in cows treated with a luteolytic prostaglandin.…”
Section: Introductionmentioning
confidence: 99%
“…The luteolytic effect of PGF2α in cattle was described by several workers in the early 1970s. In dairy cattle, several studies confirmed the capability of PGF2α and its synthetic analogues like alfaprostol (Randel, 1988), clorprostenol (Cooper and Rowson, 1975), fenprostalene (Stotts et al, 1987) and luprostiol (Plata et al, 1990) to initiate the regression of mature CL in the ovary, thus provoking and synchronizing estrus of animals. Though the estrus synchronization appeared in the world since 45 years (Baruselli et al, 2013) but there is still considerable limitation.…”
Section: Introductionmentioning
confidence: 90%
“…Neither termination of second and third trimester pregnancy in ponies or mares with prostaglandin analogues nor accompanying plasma progesterone concentrations had been reported. Analogues of PGF2a were luteolytic in horses (1) and cattle (5) and caused parturition within 3 h in mares (16) and 30 h in cows (2) near term. The purpose of this study was a) to determine if single or multiple PG F2a analogue treatments to mares during midgestation would terminate pregnancy and b) to monitor plasma progesterone changes after PGF2a analogue treatment.…”
Section: Introductionmentioning
confidence: 99%